Forms and Functions of the Self-Conscious Emotions. Issue 2 (February 2019) - Sznycer, Daniel
Abstract : Pride, shame, and guilt color our highest and lowest personal moments. Recent evidence suggests that these self-conscious emotions are neurocognitive adaptations crafted by natural selection. Specifically, self-conscious emotions solve adaptive problems of social valuation by promoting the achievement of valued actions and characteristics to increase others' valuations of the individual (pride); limiting information-triggered devaluation (shame); and remedying events where one put insufficient weight on the welfare of a valuable other (guilt). This adaptationist perspective predicts a form–function fit: a correspondence between the adaptive function of a self-conscious emotion and its information-processing structure. This framework can parsimoniously explain known facts about self-conscious emotions, make sense of puzzling findings, generate novel hypotheses, and explain why self-conscious emotions have their characteristic self-reflexive phenomenology. Highlights: Self-conscious emotions such as pride, shame, and guilt are often studied through the lens of attributional theories. Under attributional theories, the activation and operation of self-conscious emotions depend on how the individual construes and evaluates her own successes and failures. Although attributional theories highlight the intrapersonal nature of self-conscious emotions, recent theories and data suggest that the self-conscious emotions serve interpersonal adaptive functions. From an adaptationist perspective, the characteristic self-reflexive and self-evaluative processes of self-conscious emotions are proximate means to solve adaptive problems related to social valuation. Many known facts about the self-conscious emotions can be interpreted as outputs delivered by well-engineered emotion adaptations. Attributional theories view shame as an immoral, pathological version of guilt. However, shame and guilt simply appear to be distinct adaptations serving different adaptive functions. This interpersonal adaptationist framework can generate novel, testable hypotheses.